Caring for Adults with Intellectual Disability: The Perspectives of Family Carers in South Africa. Issue 6 (10th September 2015) - McKenzie, Judith; McConkey, Roy
Abstract : Background: Internationally adults with intellectual disability are largely cared for by their families, especially in low‐ to middle‐income countries (LAMIC). Compared to high‐income countries, little is known about their experiences in LAMIC such as South Africa. Methods: Focus group discussions were carried out with 37 family caregivers (FCGs) in the Cape Town metropole. These were transcribed and analysed thematically. Core categories were identified and validated through member checking. Results: Family caregivers showed strong commitment to care despite the heavy responsibility and burden of care that women especially experience. They recognize the limited personal growth opportunities for people with intellectual disability that increases the caregiving burden. FCGs identify supports and resources in the community that assist them with their care responsibilities but often feel let down by services. Conclusions: Improved family supports appropriate to the resources in LAMIC are needed especially when existing carers are no longer able to provide care.